2016
DOI: 10.14260/jemds/2016/1559
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of Ovarian Cyst During Pregnancy - A Case Report

Abstract: BACKGROUNDOvarian torsion is a rare cause of acute abdominal pain during pregnancy. Torsion usually occurs in ovaries with previously diagnosed cysts and tumours. The risk of ovarian torsion rises by 5 fold during pregnancy. Diagnosis can be difficult. Although diagnostic ultrasound is a frequently used imaging tool in patients with suspected ovarian torsion, it has a poor negative predictive value. A high clinical suspicion and early management correlate with favourable maternal and foetal outcomes. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Although the exact origin of adnexal torsion is unknown, it has been observed that a long tube and a long utero-ovarian ligament are predisposing variables. These features promote adnexal movement [4] , [9] . Potential risk factors include the use of assisted reproductive technologies, ovarian cysts and masses, ovulation inducement, and prior adnexal torsion [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact origin of adnexal torsion is unknown, it has been observed that a long tube and a long utero-ovarian ligament are predisposing variables. These features promote adnexal movement [4] , [9] . Potential risk factors include the use of assisted reproductive technologies, ovarian cysts and masses, ovulation inducement, and prior adnexal torsion [10] .…”
Section: Discussionmentioning
confidence: 99%